Territorial distribution of electoral supports in latin america: the cases of ecuador, peru and honduras (1979-2006) (2009)
Based on the classification of political party systems of Ecuador and Peru within the group of the least nationalized ones in Latin America, and Honduras as the one that shows a higher degree of nationalization, this paper works towards goals: First, explore if there has been changes or continuities related with the aforementioned level of nationalization; secondly, identify variables that can affect it. The central question involves exploring which factors are the ones that can make a party system to be more nationalized than another. The results of legislative elections celebrated between 1979 and 2006 are used here.